2015 5th International Conference on Computer and Knowledge Engineering (ICCKE) 2015
DOI: 10.1109/iccke.2015.7365862
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic malware detection using Linear Discriminant Analysis and Graph Similarity

Abstract: The most common malware detection approaches which are based on signature matching and are not sufficient for metamorphic malware detection, since virus kits and metamorphic engines can produce variants with no resemblance to one another. Metamorphism provides an efficient way for eluding malware detection software kits.Code obfuscation methods like dead-code insertion are also widely used in metamorphic malware. In order to address the problem of detecting mutated generations, we propose a method based on Opc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The Opcode data set is created by extracting Opcode density histogram during program execution. Mirzazadeh et al (2015) demonstrated how to detect metamorphic malware particularly NGVCK and MWOR using a Linear Discriminant Analysis method. The research framework was based on Opcode Graph Similarity (OGS) of Runwall et al 2015which trimmed lifeless ciphers from the graph.…”
Section: Conclusion and Further Discussionmentioning
confidence: 99%
“…The Opcode data set is created by extracting Opcode density histogram during program execution. Mirzazadeh et al (2015) demonstrated how to detect metamorphic malware particularly NGVCK and MWOR using a Linear Discriminant Analysis method. The research framework was based on Opcode Graph Similarity (OGS) of Runwall et al 2015which trimmed lifeless ciphers from the graph.…”
Section: Conclusion and Further Discussionmentioning
confidence: 99%
“…Next, we adopt a commonly used softmax function 29 to calculate the conditional probability  p o e ( ) in Equation (2). Denoting o and e as the ids of the output and input instructions, our model aims to learn the "center" vector v and the "outside" vector u for each instruction over the training corpus.…”
Section: Instruction Embedding Extractionmentioning
confidence: 99%
“…Graph based techniques are popular when dealing with the metamorphic malware characterization as they reflect the intricate resemblance between the malware family members. To capitalize this idea, an op-code based similarity between the graphs of metamorphic malware variants has been proposed by Reza et al [143]. The uniqueness of the proposed technique is attributed towards the use of Linear Discriminant Analysis (LDA) to determine discriminatory malware indicators which in this case are distinct edges that can linearly separate two classes while the rest of the redundant edges are removed.…”
Section: Recent Research Status In Mutating Malware Characterizationmentioning
confidence: 99%